When worry about climate change leads to climate action: How values, worry and personal responsibility relate to various climate actions. (May 2020) - Bouman, Thijs; Verschoor, Mark; Albers, Casper J.; Böhm, Gisela; Fisher, Stephen D.; Poortinga, Wouter; Whitmarsh, Lorraine; Steg, Linda
Highlights: Climate worry raises personal responsibility and, thereby, diverse climate actions. Individuals who strongly endorse biospheric values worry more about climate change. Personal responsibility to reduce climate change relates to various climate actions. Biospheric values primarily relate to personal climate mitigation behaviours. Worry about climate change is primarily associated with climate policy support. Abstract: The IPCC's report on Global Warming of 1.5°C positioned climate change as one of the most worrying issues mankind has ever faced. Although many people worry about climate change, there is still much unknown about the origins and outcomes of worry about climate change; particularly, whether and how it can motivate specific and personal climate actions. The current paper investigates this critical relationship with data from the European Social Survey Round 8 (44, 387 respondents from 23 countries). As expected, the more individuals worried about climate change, the more likely they were to take and support climate action. Yet, the process through which this association occurred differed between actions. Specifically, worry was both directly and indirectly, via feelings of personal responsibility to reduce climate change, associated with climate policy support; whereas worry was mostly indirectly associated with personal climate mitigation behaviours, via personal responsibility. In addition, worry about climate change appears partly rooted in biospheric values (i.e., caring about nature and the environment), and biospheric values were also clearly, directly and positively related to personal climate mitigation behaviours. The relationships were highly consistent across countries but varied somewhat in size. The results show how generic feelings about climate change can directly and indirectly affect both climate policy support and personal climate mitigation behaviours, thereby providing critical insights for science and policy making.